Encapsulation optimization and pH- and temperature-stability of the complex coacervation between soy protein isolate and inulin entrapping fish oil - Rios-Mera, Juan D. (2019)
Juan D. Rios-Mera and Erick Saldaña are grateful to the support of the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica – CONCYTEC, from Peru (CIENCIACTIVA programme, PhD scholarship contracts: No. 238-2018-FONDECYT and No. 104-2016-FONDECYT). Juan D. Rios-Mera is also grateful for the scholarship granted by Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – CAPES, from July 2017 to January 2019.